2010
DOI: 10.1177/193229681000400420
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Different Lancing Sites for Self-Monitoring of Blood Glucose: A Comparison of Fingertip Site with Palm Site Using the OneTouch® Ultra® Blood Glucose Monitoring System

Abstract: These results suggest that patients desire to use the palm for AST, but more technological advances in AST of a palm site is required to reduce patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The OneTouch Ultra by Lifescan (Johnson & Johnson) in 2001, requiring only 1 µL of sample, used glucose oxidase methodology and was one of the first glucometers to be plasma calibrated 53. The OneTouch Ultra introduced the ability to test in other sites of the body like the forearm or hand, which reduced sampling pain and increased compliance.…”
Section: Poc Testingmentioning
confidence: 99%
“…The OneTouch Ultra by Lifescan (Johnson & Johnson) in 2001, requiring only 1 µL of sample, used glucose oxidase methodology and was one of the first glucometers to be plasma calibrated 53. The OneTouch Ultra introduced the ability to test in other sites of the body like the forearm or hand, which reduced sampling pain and increased compliance.…”
Section: Poc Testingmentioning
confidence: 99%
“…88 Problem solving techniques 15 and motivational interviewing are useful strategies to increase adherence with SMBG. 89 Minimizing pain with alternative lancing devices, 90 alternative site testing, 91,92 or flash glucose monitoring systems, 93 may encourage testing. Encouraging patients to view results as "high" rather than "bad" increases testing frequency and improves HbA1c in adults and young people.…”
Section: Addressing Barriers To Technology Use and Strategies To Optimentioning
confidence: 99%
“…, Ito et al . ). Several studies have reported that blood glucose measurements taken at the forearm and thigh were less reliable in the presence of hypoglycaemia or hyperglycaemia, after a meal and after exercise because the blood glucose concentration at these sites lagged behind that at the fingertip by 30–60 minutes (Ellison et al .…”
Section: Introductionmentioning
confidence: 97%
“…The major concern about the use of alternative sampling sites is reliability because inaccuracy of the blood glucose measurements will affect the treatment and, thus, could be dangerous for clients. Empirical studies have been conducted to compare the blood glucose concentration levels at alternative body sites, such as the palm, forearm, thigh, calf and earlobe (Jungheim & Koschinsky 2002a, Bina et al 2003, Fedele et al 2003, Tieszen & New 2003, Dufaitrepatouraux et al 2004, Ferraz et al 2004, Shibata et al 2004, Toledo & Taylor 2004, Kempe et al 2005, Anzalone 2008, Knapp et al 2009, Ito et al 2010. Several studies have reported that blood glucose measurements taken at the forearm and thigh were less reliable in the presence of hypoglycaemia or hyperglycaemia, after a meal and after exercise because the blood glucose concentration at these sites lagged behind that at the fingertip by 30-60 minutes (Ellison et al 2002, Bina et al 2003, Fedele et al 2003.…”
Section: Introductionmentioning
confidence: 99%